APRESENTAÇÃO DOS CADERNOS DO IL 54 - Hoff, Patrícia Cristine; Ferreira, Cinara Pavani; Santos Solé, Alessandra; de Los Santos, Bruna da Rosa; Alquatti, Raquel; Garbin, Stefany Rettore; Simionato, Deborah Mondadori; de Freitas, Olívia Barros; da Costa, Monica Chagas (Cadernos do IL, 2017)
Apresentação do nº 54 dos Cadernos do IL - Número Especial/Estudos Linguísticos e Estudos Literários